(untitled) (Comillas Journal of International Relations, 2019)
Although the Roman Hispania already projected some typical behavior, the image of Spain abroad was consolidated in the middle of the last millennium around several features related to the hegemonic power that it reached at that time. Since then, its image has always turned around two basic and antagonistic archetypes, the Enlightenment one and the romantic one, what has generated intense and contradictory perceptions. However, at the end of the 20th century the image was already comparable to that of Western countries. In the first years of the 21st century, the image of Spain has been significantly influenced by the economic crisis, although it has remained always among the twenty countries with a better reputation. The valuation of Spain is especially high in areas related to entertainment and culture, and lower in those related to economics and technology.